2016
DOI: 10.3390/ijms17081334
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of MicroRNA-206 and Novel Mini-STR Assays for Carrier Detection in Duchenne Muscular Dystrophy

Abstract: Duchenne Muscular Dystrophy (DMD) is an X-linked neuromuscular disorder in which the detection of female carriers is of the utmost importance for genetic counseling. Haplotyping with polymorphic markers and quantitation of creatine kinase levels (CK) allow tracking of the at-risk haplotype and evidence muscle damage, respectively. Such approaches are useful for carrier detection in cases of unknown mutations. The lack of informative markers and the inaccuracy of CK affect carrier detection. Therefore, herein w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…It has previously been reported that the myomiR miR‐206‐3p is elevated in human female DMD carriers . We therefore decided to first investigate ex‐miRNA abundance in heterozygous female carrier mice.…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been reported that the myomiR miR‐206‐3p is elevated in human female DMD carriers . We therefore decided to first investigate ex‐miRNA abundance in heterozygous female carrier mice.…”
Section: Resultsmentioning
confidence: 99%
“…2 ). For instance, the characterization of circulating cell-free miRNAs in serum helps in concluding diagnostic and prognostic assessments, based on the fact that disease-specific miRNAs can be identified in extracellular body fluids (such as serum, plasma, and saliva), supporting their potential as biomarkers [ 24 27 , 30 , 33 35 ]. The presence of miRNAs in body fluids is based on the fact that extracellular miRNAs are protected by exosome-like structures and small intraluminal vesicles released by a large variety of cells [ 36 , 37 ].…”
Section: Non-coding Rnas As Possible Targets In Theranostics Of Genetmentioning
confidence: 99%
“…Recent studies have shown that circulating miRNAs can be used as potential diagnostic biomarkers for female DMD/BMD carriers (4,11). Therefore, we evaluated the ability of these seven serum myomiRs and CK to diagnose MD-carriers using ROC curve analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that ~2.5–40.0% of female carriers will have manifestations of muscular dystrophy (MD) such as muscle weakness or heart disease later on in their life, but these people rarely show symptoms during childhood ( 2 4 ). In addition, multiple studies have shown that ~45–76% of female carriers have increased serum creatine kinase (CK) levels, while others are normal ( 5 7 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation